Diminutive Review on the Ethnomedicinal Uses of Drumstick (Moringa oleifera Lam.) Tree from 1998 – 2023 - O. E. Oghama (Journal of Applied Sciences and Environmental Management, 2023)
Ethnomedicinal uses involve the comparative study of how different cultures view diseases, medical beliefs and practices of indigenous cultures on how they treat or prevent diseases. Hence, the objective of this paper is to provide a miniature review on the ethnomedical uses of drumstick (Moringa oleifera) tree by harvesting data and information from previous publications from 1998 - 2023 using online Google search. Data revealed that Moringa oleifera is also called “miracle tree” or the “tree of life,” horseradish tree or Ben oil tree. In almost all indigenous cultures, various parts of Moringa oleifera is associated as being used for treatment of a variety of health conditions ranging from wounds, skin infections, joint pain, hepatitis, ulcers, liver diseases, kidney stones, inflammation, ear and tooth pain, fever, diarrhea, hypertension, anxiety etc. It is recommended that a more elaborate literature review should be carried out dating back in times to keep an up-to-date record of ethnomedicinal uses of the plant and capture other ethnomedicinal uses of M. oleifera not included in this review.